Relaciones entre lavado de activos y delitos relativos al urbanismo. Orígenes de la perspectiva española - Núñez Paz, Miguel Ángel (2022)
It is undeniable that the relationship between urbanism and money laundering has become in a criminal constant. The other crimes that generate this laundering does not represent a significantly high figure compared with referring laundering offenses arising from the corruption, fraud and drug trafficking.